Analisis Pola Hidup Dan Dukungan Keluarga Pada Pasien Diabetes Melitus Tipe 2 Di Wilayah Kerja Puskesmas Payung Sekaki - Nopriadi; Iis Dian Saviqoh; Yesi Hasneli (STIKes Payung Negeri Pekanbaru, 2021)
Diabetes Mellitus (DM) is a metabolic disease characterized by high blood sugar levels. Type 2 DM is the most common.The reason is due to an unhealthy lifestyle, several attempts to reduce trigger factors such as regulating diet, weight control, exercising, monitoring blood sugar, directed diet, healthy and balanced nutrition. In addition, family support also affects the quality of life of DM patients. The purpose of this study was to describe the pattern of life (diet, physical activity) and family support in patients with type 2 diabetes. This research method used descriptive analytic with cross sectional design. Thesample of this study was 131 patients who were taken based on the inclusion criteria using purposive sampling. Results: Most patients were aged 56-65 years (36.6%) and mostly suffered by men (52.7%), respondents who experienced complications (91.6%) and most suffered by men (99, 9%) while the type of complication is numbness (peripheral nephropathy) (69.5%). The patient's lifestyle showed a good lifestyle (81.7) and family support showed good family support (98.5). Conclusion: A good lifestyle can also be influenced by good family support so that it makes sufferers more enthusiastic to apply healthy patterns in daily life.